A PROSPECTIVE, RANDOMIZED TRIAL COMPARING PLAIN GUT TO POLYGLACTIN 910 (VICRYL) SUTURES FOR SCLEROTOMY CLOSURE AFTER 23-GAUGE PARS PLANA VITRECTOMY. Issue 6 (June 2018) - Sridhar, Jayanth; Kasi, Sundeep; Paul, Joshua; Shahlaee, Abtin; Rahimy, Ehsan; Chiang, Allen; Spirn, Marc J.; Hsu, Jason; Garg, Sunir J.
Abstract : Purpose: To report a prospective, randomized comparative study assessing clinical outcomes of plain gut versus polyglactin 910 (PG910) sutures for sclerotomy closure after 23-gauge pars plana vitrectomy. Methods: A single-masked, randomized, prospective study was undertaken with 49 eyes of 49 patients undergoing 23-gauge pars plana vitrectomy randomized to sclerotomy closure with either plain gut suture, PG910 (Vicryl) suture or a combination of the two. Assessment was based on both a postoperative pain scale and a standardized assessment of scleral inflammation at each suture site. Results: No wound leakage was noted postoperatively in any patient. Across all groups, scleral inflammation was significantly higher at the PG910 suture sites compared with the plain gut suture sites at both the 1-week ( P = 0.04) and 1-month postoperative visits ( P < 0.001). Patients with PG910 sutures reported greater pain at the 1-month postoperative visit than those with plain gut sutures ( P = 0.018). Conclusion: This prospective study suggests improved tolerability and reduced inflammation using plain gut suture compared with an 8-0 PG910 suture to close 23-gauge sclerotomies. Abstract : This single-masked, prospective study comparing pars plana vitrectomy sclerotomy closure with plain gut versus polyglactin 910 suture material found no complications with use of either suture. Scleral inflammation and pain were significantly less with use of plain gut suture.